MARASMIC WITH FAILURE TO THRIVE AND STUNTING ACCOMPANIED PULMONARY TUBERCULOSIS AND NUTRITIONAL ANEMIA - Sayoeti, Talitha Badzlina; Pratignyo, Rogatianus Bagus (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
Marasmic is a malnutrition condition occurs when the diet is lack of calories and protein, or can also due to malabsorbtion, metabolic abnormalities or congenita l malformations. In malnutrition patients can occur growth disorder. Mortality rate quite large, about 55%. Death is often caused by an infectious disease due to a disorder of the body’s defense mechanism, this also often cause severe life-threatening condition. A 1 year old child, came with chief complaints of cough since he was 5 months with no improvement, accompanied with decreased of app etite so there is no increase in body weight. Patients also experienced subfebrile fever with night sweating. Patient had contact with pulmonary tuberculosis patient. Physical examination found pulse 140x/min, respiration 32x/menit, temperature 38,1o C (per axiler), body weight 5,4 Kg and height 65 Cm. Conjunctival pallor, elderly face, sunken eyes, baggy pants, wasting, turgor returns slowly and no edema. Blood tests found Hb 10.6 g/dL. Radiological examination overview of active pulmonary tuberculos is. Patient was diagnosed with marasmic with failure to thrive and stunting accompanied pulmonary tuberculosis and nutritional anemia. Patient was threated based on management procedure of marasmic and management of pulmonary tuberculosis based on national guidelines tuberculosis for children. Malnutririon can lead to failure to thrive, anemia and immune system distur bance that cause the patient more likely to get any infection. [J Agromed Unila 2014; 1(1):22-7] Keywords: failure to thrive, marasmic, nutritional anemia, pulmonary tuberculosis, stuntin